Adverse maternal and neonatal outcomes among singleton pregnancies in women of very advanced maternal age: a retrospective cohort study - Wu, Yuelin; Chen, Yan; Shen, Minxue; Guo, Yanfang; Wen, Shi W; Lanes, Andrea; White, Ruth R; Adanlawo, Adewumi; Walker, Mark; Hua, Xiaolin (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background There is an increasing prevalence of women who tend to delay childbirth until a very advanced age. However, there is sparse data regarding very advanced maternal age (vAMA) and the interplay between vAMA and assisted reproductive technology (ART) on adverse perinatal outcomes. The study aimed to assess the risk of adverse maternal and neonatal outcomes of vAMA women (≥43 years), and to investigate the effect of maternal age on adverse maternal and neonatal outcomes in ART pregnancies. Methods Data was obtained from a population-based retrospective cohort of women who delivered in Ontario, Canada, between April 1st, 2012 and March 31st, 2015. The adjusted relative risks (ARR) and 95% confidence intervals (CI) for adverse maternal and neonatal outcomes were estimated by using multivariate log-binomial regression models among age groups. All models were stratified by the utilization of ART (ART and spontaneous conceptions). Results Women at vAMA had a higher risk of composite outcome comprised of preeclampsia, intrauterine growth retardation, stillbirth, and placental abruption than the younger counterparts (ARR = 1.38, 95% CI: 1.23–1.55 compared to mothers aged 20–34; ARR = 1.26, 95% CI: 1.12–1.42 compared to mothers aged 35–42). Increased risk of the primary outcome in ART compared to spontaneous conception was only observed in women aged 20–34 years (ARR = 1.24, 95% CI: 1.14–1.35). For women conceived with ART, the risk for the primary outcome significantly increased in women at vAMA (ARR = 1.29, 95% CI: 1.01–1.65 compared to mothers aged 20–34; ARR = 1.36, 95% CI: 1.06–1.74 compared to mothers aged 35–42). Conclusion Women at vAMA have higher risks of adverse maternal and neonatal outcomes. Although the utilization of ART may carry an independent role for adverse perinatal outcomes, it does not further enhance the adverse effect of vAMA.